Comparison of the Effects of Interleukin-1 on Equine Articular Cartilage Explants and Cocultures of Osteochondral and Synovial Explants - Byron, Christopher R.; Trahan, Richard A. (Frontiers in Veterinary Science, 2017)
Osteoarthritis is a ubiquitous disease affecting many horses. The disease causes chronic pain and decreased performance for patients and great cost to owners for diagnosis and treatment. The most common treatments include systemic nonsteroidal anti-inflammatory drugs and intraarticular injection of corticosteroids. There is excellent support for the palliative pain relief these treatments provide, however they do not arrest progression and may in some instances hasten advancement of disease. Orthobiologic treatments have been investigated as potential osteoarthritis treatments that may not only ameliorate pain but also prevent or reverse pathologic articular tissue changes. Clinical protocols for intraarticular use of such treatments have not been optimized; the high cost of in vivo research and concerns over humane use of research animals may be preventing discovery. The objective of this study was to evaluate a novel in vitro articular coculture system for future use in osteoarthritis treatment research. Concentrations and fold increases in various markers of inflammation (prostaglandin E2 and tumor necrosis factor-alpha), degradative enzyme activity (matrix metalloproteinase-13 [MMP-13]), cartilage and bone metabolism (bone alkaline phosphatase and dimethyl-methylene blue), and cell death (lactate dehydrogenase) were compared between IL-1-stimulated equine articular cartilage explant cultures and co-cultures comprised of osteochondral and synovial explants (OCS). Results suggested that there are differences in responses of culture systems to inflammatory stimulation. In particular, the IL-1-induced fold changes in MMP-13 concentration were significantly different between OCS and cartilage explant culture systems after 96 hours. These differences may be relevant to responses of joints to inflammation in vivo and could be important to the biological relevance of in vitro research findings.